Fasilitasi Kunjungan Mahasiswa untuk Pembelajaran Budidaya Sidat (Anguilla Spp.) ke PT. Laju Banyu Semesta - Rifqi, Muhammad; Efendi, Diding Sudira; Nopiana, Medi; Rahman, Rahman; Cahyadinata, Indra; Muis, Muis; Munawar, Munawar; Handayani, Setyo (Jurnal ETAM, 2025)
The community service activity is motivated by the enormous potential for eel fisheries business in Indonesia, as seen by the market potential (especially the international market) and the opportunities to increase the production of this fish. The fact that only a few people know and understand the nutritional content and how to grow out and process eels encouraged the community service team to carry out eel fisheries learning activities at PT. Laju Banyu Semesta. Meanwhile, most of the students of the IPB University, especially students of the Faculty of Fisheries and Marine Sciences, were not yet aware of the existence of the company and eel aquaculture, strengthening the community service team to hold this activity.